Teachers’ Perception on Curriculum Penggerak at SMA Muhammadiyah Al-Amin Kota Sorong - Axelina, Mersi (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research aims to determine teachers’ perception about the Teachers’ Perception on Curriculum Penggerak at SMA Muhammadiyah Al-Amin Kota Sorong. This research is descriptive qualitative research. Data collection techniques using interview techniques. The population in this research were two female teachers as research subjects. From the result of interviews, it was found that teachers were able to demonstrate their competence in implementing the curriculum penggerak demands and the needs of students. The results of the findings above prove that the curriculum penggerak that is implemented is good enough so that it can be concluded that the curriculum penggerak is quite effective in the learning process at SMA Muhammadiyah Al-Amin Kota Sorong.